(untitled) (Journal of Social Sciences Review, 2022)
China-Pakistan Economic Corridor (CPEC) under the Belt and Road Initiative is one of the most notable collaborations (BRI) through the use of networks of roads, highways, and railroads, CPEC seeks to link China and Pakistan with the rest of the globe. CPEC will provide opportunities for the growth of the energy industry, rail and road infrastructure, and other areas. Since the bulk of the research focuses on the difficulties connected with the China-Pakistan Economic Corridor, the goal of this study is to examine the beneficial effects of this project, particularly for Pakistan (CPEC). To evaluate the contribution of CPEC to Pakistan’s sustainable economic growth, this research evaluates the relevant literature. This research suggests that the CPEC is an ambitious development project since it requires a more extensive reorganization of Pakistan’s economy. In addition to generating significant amounts of foreign direct investment for Pakistan, this project will also provide China access to a new market, which will increase its trade potential. This analysis found that the CPEC would boost regional connectivity, solve energy shortages, expand infrastructure, and foster people-to-people ties in both nations, all of which will assist to boost the tourist industry.